2015
DOI: 10.1080/1369118x.2015.1093531
|View full text |Cite
|
Sign up to set email alerts
|

Constructive activism in the dark web: cryptomarkets and illicit drugs in the digital ‘demimonde’

Abstract: Dr Barratt is an NHMRC Postdoctoral Fellow conducting research into the social and public health implications of internet technologies for people who use illicit and emerging psychoactive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 26 publications
1
71
2
1
Order By: Relevance
“…Maddox et al (2016) found that respondents after the fall of Silk Road experienced a sense of loss for the political vision of a different future (Maddox et al, 2016, p. 122). Empirically, we see this loss expressed in a declining prevalence of libertarian discourse indicating that after the fall of Silk Road, participants stopped discussing libertarian politics.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Maddox et al (2016) found that respondents after the fall of Silk Road experienced a sense of loss for the political vision of a different future (Maddox et al, 2016, p. 122). Empirically, we see this loss expressed in a declining prevalence of libertarian discourse indicating that after the fall of Silk Road, participants stopped discussing libertarian politics.…”
Section: Discussionmentioning
confidence: 96%
“…Law enforcement agencies have expressed concerns about 'going dark' and allowing 'dark, ungoverned space' as the unintended consequence of the availability of tools for encryption and privacy (Comey, 2014;Whitehead, 2014). The use and preoccupation with technologies for encryption and anonymity on cryptomarkets echo a cipherpunk ethos of either sabotaging or limiting state power through technology (Martin, 2014b;Maddox et al, 2016;May, 2001May, , 1994. Thus, there is also a political dimension that is oriented towards structure, state, and state power.…”
Section: Politics Of the Silk Road -Crypto-anarchism Libertarianism mentioning
confidence: 98%
See 1 more Smart Citation
“…Another point highlighted in our special issue is that cryptomarkets are not only places to trade drugs and other commodities or services. Silk Road was described by its creator as a technology of liberation from the dictates of the state (see Maddox, Barratt, Allen, & Lenton, 2016). Munksgaard and Demant's paper (2016) tracked libertarian discourse across online forum content, finding a sharp decline in libertarian discussion following the closure of Silk Road 1, as new cryptomarkets, perhaps built with different primary motives, took its place.…”
Section: Mapping the Innovations Of Cryptomarketsmentioning
confidence: 99%
“…The Russian government has systematically tried to disrupt some anonymising systems whereas US government agencies been more circumspect and are constrained by unresolved legal questions (Çalışkan, Minárik, & Osula, 2015). These differences and disputes highlight the dual nature of the internet, both allowing counterpublics to emerge and also opportunities for state and private domination through control of the data infrastructure (Garrett, 2006;Maddox, Barratt, Allen, & Lenton, 2016). Researchers have identified new orientations and identities coming into being on the internet such as crypto-freedom, which to an extent promotes an older vision of the internet as composed of self-reliant, technically proficient actors and peer generated communities (Beer & Burrows, 2010;Coleman & Golub, 2008).…”
mentioning
confidence: 99%